A cost-effectiveness analysis model of Preventicus atrial fibrillation screening from the point of view of statutory health insurance in Germany - Ralf Birkemeyer; Alfred Müller; Johann-Matthias von der Schulenburg (Health Economics Review, 2020)
Background: With atrial fibrillation (AF) the risk of stroke is 4.2-fold increased to a comparable population without AF. This risk decreases by up to 70% if AF is detected early enough and effective stroke preventive measures are taken as recommended by international guidelines. Long-term studies found large number of subjects with undiagnosed AF. Preventicus Heartbeats" is a hands-on screening tool for use on smartphone to diagnose AF with high sensitivity and specificity. The aim of this study is to research the cost-effectiveness of systematic screening for AF with this smartphone application. Method: Employing a Markov model we analysed the cost-effectiveness of the "Preventicus Heartbeats" screening for Germany, i.e. from the perspective of German statutory sick funds. Results: For a cohort of 10,000 insured 75-year-old the use of the diagnostic app could avoid 60 strokes in the remaining lifetime thereof 32 strokes in the next four years. Former models have applied similar cohorts. The same cohort showed an increase in quality-adjusted life years (QALY) in the remaining lifetime of 165 QALYs in the scenario with screening versus. without screening and a decrease in discounted lifetime costs (including risk compensation effects) of exteuro129 per participant ( exteuro148 for male, exteuro114 for female participants). Conclusions: The modelling demonstrates the health benefits and economic effects of an implementation of a systematic screening on AF with "Preventicus Heartbeats", given the perspective of the German payer, the statutory health care system.
Keywords: 330; Atrial fibrillation; Screening; Prevention of stroke; Cost-effectiveness analysis